Sleep duration and sleep quality in people with and without intellectual disability: A meta-analysis. (August 2018) - Surtees, Andrew D.R.; Oliver, Chris; Jones, Chris A.; Evans, David L.; Richards, Caroline
Summary: This study provides the first meta-analysis of the purported differences in sleep time and sleep quality between people with and without intellectual disabilities. Twenty-one papers were identified that compared sleep time and/or sleep quality in people with and without intellectual disabilities. The meta-analysis of sleep time revealed that people with an intellectual disability slept for 18 min less, on average, than people without an intellectual disability. This significant difference was limited to those studies that tested groups of people with an identified genetic syndrome or developmental disorder. The analysis of sleep quality also concluded that people with intellectual disabilities experienced poorer sleep: In 93% of comparisons between groups, sleep was found to be of poorer quality in the group of people with intellectual disabilities. There were no differences found between studies that measured sleep objectively and those that used diary or questionnaire measures. Notably, most samples were drawn from populations of people with specified genetic syndromes or developmental disorders, rather than intellectual disability of heterogeneous origin. Similarly, most studies investigated sleep in children, although there was no evidence that the differences between the groups reduced during adulthood. Most studies used highly-regarded objective measures of sleep, such as polysomnography or actigraphy, although methodological flaws were evident in the identification of samples and the measurement of intellectual disability.